PENGARUH PERUBAHAN KEBIJAKAN DEVIDEN TERHADAP PERUBAHAN KINERJA KEUANGAN DENGAN PERUBAHAN RASIO AKTIVITAS SEBAGAI VARIABEL INTERVENING - Nany, Magdalena; Maria, Trisni Suryarini (Jurnal Akuntansi Bisnis, 2011)
Lower dividend distribution will increase retained earnings. Higher assets will increase financial per.formance if the assets is well managed. The objective of this research was to examine whether activity ratios changes is a mediator on the association between dividend policy changes and financial performances changes or not. F((ty nine companies listed at Jakarta Stock Exchange at the end 0.( 2004 that distributed their dividends for 2004 and 2004, were analyzed by path analysis. The results show that activity ratios changes isnt a mediator on the association between dividend policy changes and financial performances changes.